A dimensão coletiva na criação: o processo colaborativo no Galpão Cine Horto - Ricardo Carvalho de Figueiredo (2007)
This research investigated the form of theatrical creation process called collaborative experiences occurred in the projects Oficinão and Cena 3x4 of Galpão Cine Horto, the latter in partnership with Maldita Cia. Investigação Teatral. The projects mark, from 1999, the first experiments in Belo Horizonte focused on the systematic reflection and the exercise of the collaborative process, in partnership with the creators from São Paulo Luis Alberto de Abreu and Antonio Araújo, among other supervisors, mentors and guests which broadcast the concept and the practice in schools and groups in the country. In this work we ask the reasona collective of artists choose the collaborative process as a means of establishing, through two mounts, O homem que não dava seta (2002) and Casa das Misericórdias (2003). Our hypothesis is that the collaborative process with interested groups and theater artists whoinvest in the theater group called because allows verticalisation of collective experience in the field of creation, as this experience is applicant in theatrical groups in their mode of production.